2011
DOI: 10.1007/s13157-010-0139-2
|View full text |Cite
|
Sign up to set email alerts
|

Salt Marsh Carbon Pool Distribution in a Mid-Atlantic Lagoon, USA: Sea Level Rise Implications

Abstract: The distribution of carbon (C) within a salt marsh may vary among vegetation zones depending on production and decomposition dynamics and organic and mineral depositional history. We examined spatial and temporal variation of plant and soil C pools within a salt marsh fringing a coastal lagoon along the mid-Atlantic coast of the U.S. The total plant C pool increased from high marsh shrub to low marsh grass dominated areas. Much of the spatial variation in plant C pool was due to fine roots and small organic ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(50 citation statements)
references
References 45 publications
(51 reference statements)
3
45
1
1
Order By: Relevance
“…This loss was evident in the upper subsurface samples (1-5 cm depth zone), wherein disturbed salt marshes showed significantly lower (~30%) amounts of organic C than undisturbed salt marsh. Additional sampling indicated that this reduction in organic C in disturbed salt marsh was due to loss of belowground plant biomass; an otherwise important component of the C stock [26]. This amount and rate of belowground biomass loss is consistent with litterbag data by Benner et al [27], who reported 55% loss of S .…”
Section: Discussionsupporting
confidence: 75%
“…This loss was evident in the upper subsurface samples (1-5 cm depth zone), wherein disturbed salt marshes showed significantly lower (~30%) amounts of organic C than undisturbed salt marsh. Additional sampling indicated that this reduction in organic C in disturbed salt marsh was due to loss of belowground plant biomass; an otherwise important component of the C stock [26]. This amount and rate of belowground biomass loss is consistent with litterbag data by Benner et al [27], who reported 55% loss of S .…”
Section: Discussionsupporting
confidence: 75%
“…[9] Despite the great attention paid to interior fresh water wetlands, especially boreal peatlands, [10] global warming has resulted in increased studies focusing on carbon sequestration in estuarine and coastal salt marshes. [11,12] Estuarine wetlands are unique ecosystems in which the land connects to the sea and fresh water meets salt water. As a result, the tidal water of estuarine wetlands has widely varying salinity.…”
Section: Introductionmentioning
confidence: 99%
“…Biomass of J. roemerianus represented approximately 82% of the total in areas where it dominated and likewise S. patens represented 77%, and S. alterniflora 85% of the biomass pools in their respective communities (Elsey-Quirk et al 2011). Total plant macro-organic N pools measured to a 30-cm depth ranged seasonally from 46 to 88 g N m −2 in the J. roemerianus-dominated zone, 74 to 136 g N m −2 in the S. patens-dominated zone, and 67 to 150 g N m −2 in the S. alterniflora-dominated zone.…”
Section: Discussionmentioning
confidence: 99%
“…We collected green leaves, new stems, 3-year old woody stems, and large and fine roots. Five entire shrubs were harvested to develop an allometric equation (e.g., Rittenhouse and Sneva 1977;Thomson et al 1998;Sah et al 2004) based upon the relationship between dry mass, crown area (CA), and the number of secondary stems (SS) originating below a 1-m height (Elsey-Quirk et al 2011). The allometric equation developed was: y=−1,511+1,705 (CA)+585 (SS).…”
Section: Experimental Designmentioning
confidence: 99%